2020
DOI: 10.38035/dijefa.v1i4.532
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Macroeconomic Factors on the Number of Corporate Sukuk Offers in Indonesia

Abstract: This study aims to analyze the effect of macroeconomics factors on corporate sukuk in Indonesia in the short and long term. The independent variable is Inflation, Economics Growth, Total Money Supply, Foreign Exchange Rate and Bank Indonesia (BI) Rate. Whereas the dependent variable is the number of sukuk corporations offered. The results of this study indicate that the Inflation, Economics Growth, Total money supply, and BI Rate have no significant effect on the number of corporate sukuk offered. While Foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
1
1
2
Order By: Relevance
“…In bond securities, Bhattacharyay (2013) found that the volatility of interest rest will reduce investors' purchasing power of sukuk. However, it is also different from the findings Ependi & Thamrin (2020) which found that the interest rate has no effect on the development of the sukuk market.…”
Section: Introductioncontrasting
confidence: 96%
“…In bond securities, Bhattacharyay (2013) found that the volatility of interest rest will reduce investors' purchasing power of sukuk. However, it is also different from the findings Ependi & Thamrin (2020) which found that the interest rate has no effect on the development of the sukuk market.…”
Section: Introductioncontrasting
confidence: 96%
“…Maka, permintaan akan instrumen investasi akan mengalami peningkatan. Pada penelitian Ependi & Thamrin (2020) menyatakan bahwa JUB tidak berpengaruh terhadap sukuk. Sedangkan pada penelitian Ardiansyah & Lubis (2017) serta Nafisah et al (2020) menyatakan bahwa jumlah uang beredar memiliki pengaruh pada sukuk.…”
Section: Pendahuluanunclassified
“…Dalam Islam, murabahah merupakan jual beli yang tidak semerta-merta hanya untuk mencari untung tapi sebagai sarana tolong-menolong sesama umat muslim (Ependi and Thamrin, 2021). Salah satu ayat Al-Qur'an yang memperbolehkan terjadinya jual beli (murabahah) adalah firman Allah dalam surat Al-Baqarah ayat 275 : (Muhammad, 2005).…”
Section: Penulisunclassified